Cover Picture: Unusual O‐Bridged Symmetric Quinoline‐Based Ligand for the Formation of Luminescent Mono‐Aqua Lanthanide Complexes (ChemistrySelect 21/2016). Issue 21 (9th December 2016) - Hammoud, Hassan; de Bettencourt‐Dias, Ana; Schmitt, Martine; Monteiro, Jorge H. S. K.; Rossini, Jeffrey S.; Lecointre, Alexandre; Gallet, Sébastien; Bourguignon, Jean‐Jacques; Mameri, Samir
Abstract : The cover picture shows the ultraviolet (UV) irradiation of a novel sophisticated chromophore‐containing ligand chelated to luminescent trivalent lanthanide metal ion i.e., Europium(III) or Terbium(III). This ligand is based on two O‐bridged quinolines bearing carboxylate moieties to reinforce both the coordination to the central metal ion and the solubility in water solutions. The ligand functions as an 'antenna' which absorbs incident light and transfers the excitation to the central metal ion, which then deactivates by undergoing its typical luminescent emission (visible). Thus, this paper reports the efficient 7‐step methodology developed for the synthesis of this new heterocycle which was characterized in the solid state and in solution, and it reports the study of its coordination and sensitization ability for lanthanide ions in aqueous solution. Notably, the resulting mononuclear complexes are stable and display in other respects interesting luminescence quantum yields and lifetimes in water solution, e.g. 9.5% and τ = 523μs, for Eu(III). More information can be found in the Full Paper by De Bettencourt‐Dias and Mameri et al. (DOI:10.1002/slct.201601223 ). (Design: Dr. Samir Mameri and Dr. Hassan Hammoud).